2015
DOI: 10.1001/jamasurg.2014.2257
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Postoperative Mortality Among Individuals With HIV Infection Receiving Antiretroviral Therapy and Procedure-Matched, Uninfected Comparators

Abstract: IMPORTANCE Antiretroviral therapy (ART) has converted human immunodeficiency virus (HIV) infection into a chronic condition, and patients now undergo a variety of surgical procedures, but current surgical outcomes are inadequately characterized. OBJECTIVE To compare 30-day postoperative mortality in patients with HIV infection receiving ART with the rates in uninfected individuals. DESIGN, SETTING, AND PARTICIPANTS Retrospective analysis of nationwide electronic medical record data from the US Veterans Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 68 publications
(86 reference statements)
1
28
1
Order By: Relevance
“…The incidence rate ratio for postoperative sepsis in HIV-positive versus HIV-negative participants was 1.035 (95% CI 0.319-3.29; P = 0.47). King et al in a similar study done in a veterans' hospital in the USA found an incidence rate ratio of 2.11 (95% CI 1.41-3.17; P < 001) [9]. This rate was higher than that in our study possibly because they followed-up patients for a longer period.…”
Section: Discussioncontrasting
confidence: 71%
“…The incidence rate ratio for postoperative sepsis in HIV-positive versus HIV-negative participants was 1.035 (95% CI 0.319-3.29; P = 0.47). King et al in a similar study done in a veterans' hospital in the USA found an incidence rate ratio of 2.11 (95% CI 1.41-3.17; P < 001) [9]. This rate was higher than that in our study possibly because they followed-up patients for a longer period.…”
Section: Discussioncontrasting
confidence: 71%
“…Several small series and cohorts have reported treatment effectiveness estimates and complication rates for lung cancer therapies in HIV infected patients. Surgical resection is the standard-of-care for early stage lung cancer, and a large ART-era analysis from the Veterans Affairs Health System found that HIV infected patients may continue to experience more frequent surgical complications than uninfected patients[49], although results specific to lung cancer surgery were limited. A comparative study evaluating lung cancer surgical outcomes in a cohort of 22 HIV infected patients compared to uninfected comparators demonstrated more frequent surgical complications and poorer post-surgical survival[25].…”
Section: Lung Cancer Treatment and Prognosismentioning
confidence: 99%
“…All the established preoperative risk factors for PPRO in noncardiac surgery patients identified in the studies of Kheterpal et al (5,6) were found to be independently associated with a higher risk of PPRO in this study. a CD4 cell count of >200/µL was equivalent to that of an uninfected patient aged >16 years, whereas the mortality risk in a patient with a CD4 cell count of >50/µL was equivalent to that of an uninfected patient aged >47 years (8). It is therefore possible that adequate management of HIV infection in our study population resulted in no overall difference in the levels of risk for PPRO observed between HIV-infected and HIV-uninfected patients.…”
Section: Discussionmentioning
confidence: 83%